Millian Liberalism and Extreme Pornography. Issue 2 (4th December 2015) - Cowen, Nick
Abstract: How sexuality should be regulated in a liberal political community is an important, controversial theoretical and empirical question—as shown by the recent criminalization of possession of some adult pornography in the United Kingdom. Supporters of criminalization argue that Mill, often considered a staunch opponent of censorship, would support prohibition due to his feminist commitments. I argue that this account underestimates the strengths of the Millian account of private conduct and free expression, and the consistency of Millian anticensorship with feminist values. A Millian contextual defense of liberty, however, suggests several other policy approaches to addressing the harms of pornography.